Drug repurposing for schistosomiasis: Combinations of drugs or biomolecules - Gouveia, M (2018)
Schistosomiasis is a major neglected tropical disease. Control of schistosomiasis currently relies on a single drug, praziquantel, and despite its efficacy against the all schistosome species that parasitize humans, it displays some problematic drawbacks and alone is ineffective in counteracting adverse pathologies associated with infection. Moreover, due to the development of the potential emergence of PZQ-resistant strains, the search for additional or alternative antischistosomal drugs have become a public health priority. The current drug discovery for schistosomiasis has been slow and uninspiring. By contrast, repurposing of existing approved drugs may offer a safe, rapid and cost-effective alternative. Combined treatment with PZQ and other drugs with different mode of action, i.e., antimalarials, shows promise results. In addition, a combination of anthelminthic drugs with antioxidant might be advantageous for modulating oxidative processes associated with schistosomiasis. Herein, we review studies dealing with combination therapies that involve PZQ and other anthelminthic drugs and/or antioxidant agents in treatment of schistosomiasis. Whereas PZQ combined with antioxidant agents might or might not interfere with anthelminthic efficacy, combinations may nonetheless ameliorate tissue damage and infection-associated complications. In fact, alone or combine with other drugs, antioxidants might be a valuable adjuvant to reduce morbidity and mortality of schistosomiasis. Therefore, attempting new combinations of anthelmintic drugs with other biomolecules such as antioxidants provides new avenues for discovery of alternatives to PZQ.